Collision-free planning algorithm of motion path for the robot belt grinding system. (17th August 2018) - Zhang, Tie; Su, Jiewen
Collision may occur during the grinding of a workpiece by a robot sand belt. To solve this problem, a collision-free planning algorithm for the robot motion path is developed based on the collision layer method. Collision-free planning of the robot motion path is studied, and a means to adjust the machining frame on the belt is determined (i.e. moving along the axis of the belt and rotating around the tangent line). The planning curve is rapidly found on the collision layer using neighborhood search and recursive methods, and the amount of collision detection is significantly reduced. The planning curve is transformed into the robot motion path. Simulation and experimentation show that the amount of collision detection required by the proposed algorithm is 3.86% less than that required by a method using a complete collision layer. Moreover, the robot grinds the workpiece without collision. The proposed method is simple, stable, and easy to implement and possesses a good engineering application value.